Biopshychosocial and Economic Determinants of Personal Hygiene in the Prevention of Diarrheal Diseases in Sragen District, Central Java - Hervindita Dinda Siswandwika; Bhisma Murti; Ruben Dharmawan (Journal of Health Promotion and Behavior, 2017)
Background: Poor environmental sanitation and personal hygiene have been shown to be associated with increased risk of diarrheal disease. Poor personal hygiene that is associated with an increased risk of diarrheal disease may be explained by the constructs  of Health Belief Model, such as perceived susceptibility and perceived seriousness. This study aimed to examine biopshychosocial and economic determinants of personal hygiene in the prevention of diarrheal diseases.Subjects and Method: This was an analytic observational study with case control design. This study was conducted at Mondokan, Gesi, and Sambungmacan Health Centers, Sragen District, Central java, from January to March, 2017. A sample of 150 subjects, consisting of  50 cases of diarrheal disease during the past month and 100 subjects without diarrheal disease, was selected in this study by purposive sampling. The dependent variable was prevention behavior of diarrheal disease. The independent variable included perceived susceptibility, seriousness, threat, benefit, barrier, cues to action, and self-efficacy. The data was collected using a pre-tested questionnaire, and analyzed by path analysis model.  Results: There were positive, and statistically significant effects of perceived seriousness (b= 0.26; SE=0.06; p= <0.001), threat (b= 0.29; SE=0.06; p= <0.001), benefit (b= 0.21; SE= 0.06; p= <0.001), barrier (b= -0.12; SE= 0.08; p= 0.032), cues to action (b= 0.17; SE= 0.07; p= 0.003), and self-efficacy (b= 0.28; SE= 0.14; p= <0.001) on prevention behavior of diarrheal disease. There were positive, indirect, and statistically significant effect of perceived susceptibility (b= 0.55; SE= 0.06; p= <0.001), seriousness (b= 0.34; SE= 0.06; p= <0.001), and benefit (b= 0.12; SE= 0.07; p= 0.025) on prevention behavior of diarrheal disease, via perceived threat.Conclusion: Perceived seriousness, threat, benefit, barrier, cues to action, and self-efficacy, are direct determinants of prevention behavior of diarrheal disease. Perceived susceptibility, seriousness, and benefit, are indirect determinants of prevention behavior of diarrheal disease.Keyword: Biopshychosocial and economy, personal hygiene, Health Belief ModelCorrespondence: Hervindita Dinda Siswandwika. Masters Program in Public Health, Sebelas Maret University. Email: vindy_7@yahoo.com. Mobile: +6282136242777.Journal of Health Promotion and Behavior (2017), 2(1): 1-14https://doi.org/10.26911/thejhpb.2017.02.01.01